Development of creative mindset in students in the course of vocational education - Lunyachek, V. (Problems of Engineer-Pedagogical Education, 2019)
The paper considers the problems of forming the creative thinking of students of higher education institutions as solutions to the challenges of the modern labour market. The analysis of the works of leading world experts in the field of education and materials of the World Economic Forum for 2018 has been carried out. The emphasis is on the formation of separate special competencies of students in the process of studying the discipline "Creative Technologies of Education" at the Bachelor level in the Ukrainian Engineering and Pedagogical Academy. The conclusion has been made on the necessity of the transformation of the mentality of teachers of higher education institutions regarding the filling and organization of the educational process taking into account the needs of the labour market in the conditions of the fourth technological revolution. Attention is focused on the need for students to familiarize themselves with the technology transfer process, as a result of the commercialization of the process of creating innovations, motivating students to personal innovation development. The necessity of transformation of mental models of training specialists on the basis of a system approach is emphasized.